Characterisation of Wickerhamomyces anomalus and Kazachstania aerobia : investigating fermentation kinetics and aroma production - Lombard, Judith (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc)--Stellenbosch University, 2016.